2019
DOI: 10.1111/vru.12775
|View full text |Cite
|
Sign up to set email alerts
|

CT measures of lumbosacral paraspinal muscle size are not correlated with CT measures of lumbosacral stability in military working Labrador Retrievers

Abstract: Management of degenerative lumbosacral stenosis in military working dogs more frequently utilizes core conditioning exercise programs. Future research on the effectiveness of these programs may benefit from an improved understanding of relationships between paraspinal muscle size and lumbosacral stability. The aim of this retrospective, secondary analysis, cross-sectional study was to test the following hypotheses related to CT measures: (a) transverse paraspinal muscle area ratios differ between hip flexion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…For comparative purposes, the sagittal IVF areas between L1 and L6 were measured as reported previously 10 . Data collected were compared to those obtained in a pilot study of skeletally mature and gender‐matched English Springer Spaniels (unpublished data).…”
Section: Investigationsmentioning
confidence: 99%
“…For comparative purposes, the sagittal IVF areas between L1 and L6 were measured as reported previously 10 . Data collected were compared to those obtained in a pilot study of skeletally mature and gender‐matched English Springer Spaniels (unpublished data).…”
Section: Investigationsmentioning
confidence: 99%
“…Previous studies reported that caudal cervical AP (from C5 to T1) were more frequently enlarged 5,9,14 . In companion animals and humans, the assessment of IF narrowing relies mainly on cross‐sectional imaging (CT or MRI) and various measurements have been described to objectively assess the dimensions of the IF; this includes the height, width, cross‐sectional area (CSA), and volume of the IF 15–24 . In humans, APCSA measured using MRI was a good predictor of cervical IF stenosis which was easy to use and fast to measure 25 .…”
Section: Introductionmentioning
confidence: 97%
“…5,9,14 In companion animals and humans, the assessment of IF narrowing relies mainly on crosssectional imaging (CT or MRI) and various measurements have been described to objectively assess the dimensions of the IF; this includes the height, width, cross-sectional area (CSA), and volume of the IF. [15][16][17][18][19][20][21][22][23][24] In humans, APCSA measured using MRI was a good predictor of cervical IF stenosis which was easy to use and fast to measure. 25 CT measurement of IFCSA in sagittal plane have been proven useful for diagnosing and to help predicting the operability of people with lumbosacral IF stenosis.…”
Section: Introductionmentioning
confidence: 99%